CROSS-CULTURAL CONTRADICTIONS: THE MARGINALIZATION OF SOCIAL GROUPS (Academicia Globe: Inderscience Research, 2023)
The article is devoted to the study of the concepts of "marginal", "marginality" and "marginal culture". The object of research is the cross-cultural space of modern society. The author seeks to define the boundaries of these concepts, to identify common features in them and to identify specifics. The reasons for the appearance of the phenomenon of marginality, as well as the connection of marginal culture with the dominant culture and the phenomena of subculture and counterculture are considered. Also, the researcher describes and justifies the state of marginal status in the social structure of the world community.